ASSOCIATION OF GENDER AND AGE WITH COMPLIANCE OF H PYLORI ERADICATION THERAPY - Hafeez, Muhammad; Yousaf, Iftekhar; Siddiqi, Fuad `Ahmad; Hassan, Fayyaz; Khan, Muhammad Alamgir; Saeed, Farrukh (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out association of gender and age with compliance of H Pylori eradication therapy.Study Design: Cross sectional comparative study.Place and Duration of Study: Combined Military Hospital, Multan and Pak Emirates Military Hospital,Rawalpindi, from Sep 2017 to Feb 2020.Methodology: Two hundred and fifty patients with dyspepsia were included through convenient sampling after getting informed consent. The patients already under H Pylori eradication therapy were excluded from the study. Diagnosis of H Pylori infection was done by histopathology report of gastric mucosal biopsy on upper GI endoscopy in some individuals and H Pylori antigen on stool examination in others. They were placed in eight different groups keeping in mind their previous history of use of antibiotics and known side effects with the particular antibiotic.Results: There were 154 (61.60%) males and 96 (38.40) females with mean age of 36.71 ± 13.23 years. Thefrequency of male patients who complied to treatment (130/84.4%) was significantly higher as compared to the frequency of female patients (71/74.0%) at p-value of 0.04 and odds ratio of 1.9 (1.01-3.58). The study also showed that the difference of mean age between the patients who completed and those who did not complete the treatment was statistically not significant (36.33 ± 12.78 vs 38.24 ± 14.94 years).Conclusion: Compliance to H Pylori eradication therapy is associated with gender but not with age.